Professional training and development: The bedrock of ethical, competent, and sustainable sport psychology. Issue 3 (3rd July 2023) - Quartiroli, Alessandro; Fogaça, Janaina Lima; Wagstaff, Christopher R. D.
Abstract: To ensure public safety, duty of care, and professional advancement, scholars need to consider the competence, ethical practice, and well-being of sport psychology practitioners (SPPs). Despite the growth of sport psychology as a profession, scholars have predominantly focused on how to do applied sport psychology, with issues of professional formation, development, maturation, and SPPs' well-being receiving limited attention. Yet, to safeguard the future of the field, we must better understand how SPPs develop as individuals and as professionals, the contextual factors that may affect their development, and how training and supervision may contribute to professionals' experiences and development. In this invited article, we review "what we know" and "what we need to know" regarding the professional development of SPPs. In doing so, we hope to inform the reader on the critical developments in this area while presenting a commentary that facilitates discourse and future action.   Lay summary: A field that aims to grow and evolve must understand the development of ethical and competent professionals. To aid in this understanding, we provide an overview of what we know and what we need to know about the development of sport psychology professionals. IMPLICATIONS FOR PRACTICE: SPPs need to focus their attention on the development of themselves as persons and professionals regarding their competence development. SPPs may need to integrate who they are with what they do to promote an enriching, sustainable, competent, ethical, and effective practice. Supervisors on graduate and training programs should be aware of practitioner developmental processes and the factors that influence this for SPPs. Those leading training programs might adopt a developmental approach within their curricula, with priority given to assisting trainees to integrate their personal beliefs and professional philosophy into their service delivery.